2018
DOI: 10.1101/291385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coding and non-coding RNA dysregulation in bipolar disorder

Abstract: office 4.127 (Stratenum), HP 4.205 | 3584 CG Utrecht | The Netherlands | +31 (0)88 75 68638 | j.luykx@umcutrecht.nl Word count abstract: 192 Word count manuscript: 3146 Number of figures: 3 Number of tables: 1 Running title: Coding and non-coding RNAs in bipolar disorder. AbstractThe molecular mechanisms underlying bipolar disorder (BPD) have remained largely unknown. Postmortem brain tissue studies comparing BPD patients with healthy controls have produced a heterogeneous array of potentially implicated prote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…circRNA decoy activity for HUD might suggest a role of circHomer1 in the regulation of alternative splicing in normal and pathological conditions. Another recent study shows that the differential expression of circRNA observed in the frontal gyrus of patients with bipolar disorder is associated with an overall dysregulation of AS [109]. In the overall, studies reported in Table 2 suggest that, in psychiatric disorders, a circRNA general dysregulation correlates with a global change in AS [87,110,111].…”
Section: Circrnas In Neuronal Disordersmentioning
confidence: 93%
“…circRNA decoy activity for HUD might suggest a role of circHomer1 in the regulation of alternative splicing in normal and pathological conditions. Another recent study shows that the differential expression of circRNA observed in the frontal gyrus of patients with bipolar disorder is associated with an overall dysregulation of AS [109]. In the overall, studies reported in Table 2 suggest that, in psychiatric disorders, a circRNA general dysregulation correlates with a global change in AS [87,110,111].…”
Section: Circrnas In Neuronal Disordersmentioning
confidence: 93%